2021
DOI: 10.1111/jgh.15561
|View full text |Cite
|
Sign up to set email alerts
|

Role of the inflammasome, gasdermin D, and pyroptosis in non‐alcoholic fatty liver disease

Abstract: Pyroptosis is a type of programmed cell death mediated by a multiprotein complex called the inflammasome through the pro-inflammatory activity of gasdermin D. This study aimed to recognize the final biological product that leads to pore formation in the cell membrane, lysis, pro-inflammatory cytokines release, and the establishment of an immune response. An exhaustive search engine investigation of an elevated immune response can induce a sustained inflammation that directly links this mechanism to non-alcohol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 64 publications
(83 reference statements)
0
11
0
Order By: Relevance
“…It has been reported that caspase-11 mediates hepatocyte pyroptosis and promotes the progression of MCD diet-induced NASH/NAFLD [ 80 ]; and inflammasome-gasdermin D-pyroptosis [ 81 ] may regulate the progression of NASH/NAFLD [ 82 ]. In addition to promoting inflammation by enzymatic cleavage of pre-IL-1 β , pre-IL-18, and N-terminal GSDMD, caspase-1 also cleaves as many as 114 substrates, suggesting that caspase-1 may regulate inflammation indirectly via all the protein substrate-mediated signaling [ 15 ], 38 interaction protein-mediated signaling [ 15 ], and GSDMD-secretome-mediated signaling [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that caspase-11 mediates hepatocyte pyroptosis and promotes the progression of MCD diet-induced NASH/NAFLD [ 80 ]; and inflammasome-gasdermin D-pyroptosis [ 81 ] may regulate the progression of NASH/NAFLD [ 82 ]. In addition to promoting inflammation by enzymatic cleavage of pre-IL-1 β , pre-IL-18, and N-terminal GSDMD, caspase-1 also cleaves as many as 114 substrates, suggesting that caspase-1 may regulate inflammation indirectly via all the protein substrate-mediated signaling [ 15 ], 38 interaction protein-mediated signaling [ 15 ], and GSDMD-secretome-mediated signaling [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Based on literature mining, 21 , 22 , 23 , 24 a total of 33 genes that were related to pyroptosis were identified (Table S1 ). The expression of 33 PRGs was extracted and compared between 502 HNSCC and 44 normal samples using the “limma” and “pheatmap” package from TCGA‐HNSC cohort.…”
Section: Methodsmentioning
confidence: 99%
“…Liver is composed of a variety of cells including hepatocytes and nonparenchymal cells. In addition to the cells described in this review, inflammasome is also expressed in liver sinusoidal endothelial cells, myofibroblasts, dendritic cells, neutrophils and other cells in liver 68 …”
Section: Main Hepatic Cells Undergoing Pyroptosis In Liver Fibrosismentioning
confidence: 99%
“…In addition to the cells described in this review, inflammasome is also expressed in liver sinusoidal endothelial cells, myofibroblasts, dendritic cells, neutrophils and other cells in liver. 68 These cells all participant in the process of liver injury, but whether they can induce pyroptotic cell death to regulate liver inflammation and fibrosis is still unknown and needs further investigation.…”
Section: Main Hepatic Cells Undergoing Pyroptosis In Liver Fibrosismentioning
confidence: 99%